2021
DOI: 10.1016/j.esmoop.2021.100048
|View full text |Cite
|
Sign up to set email alerts
|

Gender influence on work satisfaction and leadership for medical oncologists: a survey of the Spanish Society of Medical Oncology (SEOM)

Abstract: Background Women represent an increasing proportion of the oncology workforce; however, globally this does not translate into leadership roles, reflecting disparities in career opportunities between men and women. The Spanish Society of Medical Oncology (SEOM) undertook a survey to investigate gender disparity in the Spanish oncology context. Design An online survey was made available to SEOM medical oncologists between February and May 2019. It included demographics, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
2
8
1
Order By: Relevance
“…With respect to PhD degrees and professorship positions, our finding in gynecologic oncology surgery are in contradiction to data reported in medical oncology by Elez et al. ( 24 ), who did report on a gender gap, while we did not reveal a gender disparity in our survey. However, our analysis showed that male published more than female.…”
Section: Discussioncontrasting
confidence: 99%
“…With respect to PhD degrees and professorship positions, our finding in gynecologic oncology surgery are in contradiction to data reported in medical oncology by Elez et al. ( 24 ), who did report on a gender gap, while we did not reveal a gender disparity in our survey. However, our analysis showed that male published more than female.…”
Section: Discussioncontrasting
confidence: 99%
“…More women (41 vs. 9%) felt that parenthood affected their careers adversely than men. 9 A smaller survey from the Middle East and North Africa exploring gender equality in the workplace had 64% of women reporting that their gender had a moderate to significant impact on their careers. However, 54% of women were in managerial positions.…”
Section: How Vast Is the Gender Gap?mentioning
confidence: 99%
“…In addition to mentorship sessions and a specific W4O fora at ESMO congresses, there are ongoing and completed studies to measure and monitor the gender disparity in the oncology world. 1,[5][6][7]9 Collaborative work with the national women oncology networks helps bridge the gap between women and men. Tackling gender inequality further, W4O addresses the women issues from the grassroot level by mentorship and roundtable social media discussions that will bring to light the gender gaps at all career levels.…”
mentioning
confidence: 99%
“…However, other studies have shown that just a minority of female oncologists have leadership roles, even when they represent the majority of clinical teams' workforce. 9,10 Although most medical students stated that their school offered activities and courses focused on oncology as part of their curricula, only an alarming minority (35%) considered them good or excellent. Of note, these results could not adequately reflect the perception of most medical students regarding oncology training as most universities in Latin America give oncology courses in the latest years of the medical career, and the majority of OSIGs members were coursing the first years of medical school.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have shown that just a minority of female oncologists have leadership roles, even when they represent the majority of clinical teams' workforce. 9 , 10 …”
Section: Discussionmentioning
confidence: 99%